Empirically estimated impacts of climate change on global crop production via increasing precipitation-evapotranspiration extremes - David A. Raitzer; Joeffrey Drouard (Asian Development Bank (ADB), 2024)
Although agriculture is often considered vulnerable to climate change, recent gridded crop growth modelling intercomparison exercises have found that staple crop yields will be modestly affected by global warming. However, those crop growth models also do not fully reflect impacts of increasing climate extremes. This paper uses global remote sensing-derived yield and agrometeorological reanalysis data to construct a grid cell panel at 0.1-degree resolution for 2003-2015. Regressions that control for grid cell-specific intercepts and time trends, temperature, rainfall, and cloudiness empirically estimate the relationship between yields and precipitationevapotranspiration extremes for each growing season of rice, wheat, and maize by subregion. Estimated coefficients are applied to projections from an ensemble of global circulation models to project potential losses from climate change. All crops are found as having substantial potential future global yield reductions, but reductions are highest for wheat and maize, with losses most pronounced in Southern Asia and Southern Africa.
Keywords: Q12; Q15; Q54; D22; 330; agriculture; climate change; drought; yield loss